2008
DOI: 10.1002/jrs.1915
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Raman and fluorescence spectroscopy for the assessment of the effects of the exposure to light on films of egg white and egg yolk

Abstract: In this work, non-destructive techniques were employed for the spectrofluorimetric and micro-Raman differentiation of solid films of egg yolk and egg white as a function of exposure to light. Using both techniques it is possible to discriminate between the samples on the basis of composition and follow some chemical changes involved during the light-ageing of egg proteins and fatty acid esters. In egg white, fluorescence emission spectra highlighted the presence of multiple fluorophores, with an effective broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…It is noteworthy that the equivalent fresh samples analysed in our previous study [29] generally did not display such prominent fluorescence backgrounds, and thus this appears to arise to some extent as a result of ageing. The differences in features observed here between naturally-and artificially-aged paints are quite similar to the observations of Osticioli et al [42] from fluorescence-spectroscopy studies, although these were performed with a 230 nm excitation-laser wavelength, and the fluorescence was observed at 380 nm (26,316 cm -1 , a response attributed to the amino acid tryptophan), i.e. far from the spectral region being analysed in the present work.…”
Section: Background Fluorescencesupporting
confidence: 82%
“…It is noteworthy that the equivalent fresh samples analysed in our previous study [29] generally did not display such prominent fluorescence backgrounds, and thus this appears to arise to some extent as a result of ageing. The differences in features observed here between naturally-and artificially-aged paints are quite similar to the observations of Osticioli et al [42] from fluorescence-spectroscopy studies, although these were performed with a 230 nm excitation-laser wavelength, and the fluorescence was observed at 380 nm (26,316 cm -1 , a response attributed to the amino acid tryptophan), i.e. far from the spectral region being analysed in the present work.…”
Section: Background Fluorescencesupporting
confidence: 82%
“…The bands at 1601, 1582, 1448, 1320, 874 and 755 cm -1 in the Raman spectra are assigned to the binding medium, attributable to egg yolk [39][40][41]. These results are supported by the availability of eggs from wild birds, such as geese or ducks in ancient Egypt, while domestic chickens were not introduced until classical times.…”
Section: Binding Mediummentioning
confidence: 81%
“…The results of this study give some insights into the molecular mechanisms by which catechin will prove beneficial for cell protection from free radical-and metal-induced deleterious effects. Osticioli et al [93] reported on a micro-Raman and fluorescence spectroscopic study for the assessment of the effects of light exposure on films of egg white and egg yolk. The purpose of a report by Kinoshita et al [94] was to elucidate the mechanism of sialolith formation, a cause of salivary gland infections, by using Raman micro-spectroscopy to analyse the precise distribution of phosphate and amide III in sialoliths.…”
Section: Biomoleculesmentioning
confidence: 99%